Regulation of the oncodevelopmental expression of type 1 chain ABH and Lewis(b) blood group antigens in human colon by alpha-2-L-fucosylation - Orntoft, T F; Greenwell, P; Clausen, H; Watkins, W M (Gut, 1991)
Blood group antigen expression in the distal human colon is related to the development of the organ and is modified by malignant transformation. To elucidate the biochemical basis for these changes, we have (a) analysed the activity of glycosyltransferases coded for by the H, Se, Le, X, and A genes, in tissue biopsy specimens from normal and malignant proximal and distal human colon; (b) characterised the glycosphingolipids expressed in the various regions of normal and malignant colon by immunostaining of high performance thin layer chromatography plates; and (c) located the antigens on tissue sections from the same subjects by immunohistochemistry. In both secretors and non-secretors we found a significantly higher activity of alpha-2-L-fucosyltransferases in carcinomatous rectal tissue than in tissue from normal subjects, whereas the other transferase activities studied showed no significant differences. The acceptor substrate specificity suggested that both the Se and the H gene dependent alpha-2-L-fucosyltransferases are increased in carcinomas. In non-malignant tissue the only enzyme which showed appreciably higher activity in caecum than in rectum was alpha-2-L-fucosyltransferase. Immunochemistry and immunohistochemistry showed alpha-2-L-fucosylated structures in normal caecum from secretors and in tumour tissue from both secretors and non-secretors. We conclude that the alpha-2-L-fucosyltransferases control the expression of ABH, and Lewis(b) structures in normal and malignant colon.